As a matter of standard for Asia and beyond? - LIU, Kung-Chung (Institutional Knowledge at Singapore Management University, 2019)
With the rise of the fourth industrial revolution, the internet of things, 5G, driverless vehicles and artificial intelligence all rely on interconnectivity, and more and more new standards and SEPs will emerge, making the issue of FRAND licensing of SEPs even more pressing. Asian economies are without exception standard-takers rather than standard setters. Some standards for FRAND licensing of SEPs are converging in major Asian jurisdictions such as Japan, Korea, the PRC, Taiwan and India. Worth reflecting on is whether these standards can be extended to reach beyond Asia, as many concrete undertakings made to the Chinese competition authorities by conglomerates that are operating and licensing globally, such as Qualcomm and InterDigital, have the potential of becoming binding on a worldwide scale; and how conflicts between different legal standards can be solved. We argue that the FRAND licensing of SEPs needs ex ante regulation, at least in Asia, for three reasons: global litigation indicates massive market failure and SEPs equal monopoly or joint monopoly, de facto standards are overtaking de jure standards, and SSOs from the private sector are replacing sovereign states in the development and adoption of new standards. Therefore we propose de lege ferenda for patent and competition laws and advocate that the conflicts between different legal standards can be solved not by preferring one set of standard over the other, but at best through empathy for the differences as to where they are coming from and leading to, and mutual respect for nation states’ choice about the path and standard that best suit their developmental need and paradigm system. The chapter ends by debunking some myths at the intersection between IP and competition laws.